Penerapan Kombinasi Metode SWARA dan MAUT Dalam Seleksi Penerimaan Calon Guru - Wahyudi, Agung Deni; Sulistiyawati, Ari (Jurnal Media Borneo, 2024)
The selection process for teacher candidates is a critical step in ensuring the quality of quality education for students. In addition to assessing academic qualifications such as educational background and work experience, selection should also consider aspects such as communication skills, interpersonal skills, ability to manage classes, and dedication to the education profession. The main problem in the selection of teacher candidates is the difficulty in assessing qualitative aspects such as teaching skills, interpersonal communication, and leadership. The purpose of the research on the application of the combination of SWARA and MAUT methods in the selection of teacher candidate admissions is to develop a more effective and comprehensive approach in the selection process for teacher candidate admission. By combining the SWARA and MAUT methods, this study is to improve the objectivity and accuracy of assessment of teacher candidates based on established criteria. In addition, this study is also to understand the implications of the combination of these two methods on the final decision in the selection of teacher candidates, as well as to provide a strong theoretical foundation to improve the HR selection process in the field of education. The ranking results showed that the first highest score of 0.7043 was obtained by GY candidates and was entitled to 1st place, the second highest score of 0.5804 was obtained by AJ candidates and was entitled to 2nd place, and the third highest score of 0.5365 was obtained by MS candidates and was entitled to 3rd place in the selection of teacher candidate admissions. The results of ranking using a combination of SWARA and MAUT methods are recommendations for schools in the selection of teacher candidates.